The poetic image and its aesthetics in Al-Mustadrak’s book on the makers of Andalusian collections and collections of poetry (Journal of the College of Basic Education, 2022)
This study aims at navigating and diving in the sea of ​​poetic image, its aesthetics, and patterns, in Andalusian poetry, which the investigators of poets’ collections unintentionally overlooked, and the collection of other texts in the book of Dr. Sayer. The reason for choosing this title lies in the researchers' failure to study most of the texts in this book, and to reveal their features, which are beautiful texts rich in elements of creativity. As it is known to most researchers and critics, the image is one of the most important components and elements of the poetic text. Its concept, elements, and types, ancient and modern. The image in poetic texts varied between a sensory one that depends on a sense, or more than one of the human senses, and through the senses, the recipient can stand at the picture drawn by the creator with his deep imagination, and perceive it to reach its mind, its parts, and its components, and link it to all its components. And thinking, in perceiving and comprehending it, we have walked the path of the analytical method in interrogating the poetic texts that we have chosen for study, and their interpretation, taking advantage of the technical method; In order to complete the process of discovery and extraction of the image, which we aspire to, the study was divided into an introduction and two chapters, accompanied by a conclusion, sources and references. their opinions on it.